Acquiring Scientific Skills through Science Education in Schools: A Critical Reflection - VISHWAKARMA, SUDHA; SINGH, SUNIL KR (THE PRIMARY TEACHER, 2015)
Science Education is an important part of the curriculum in schools. Science education enhances children’s knowledge and understanding of themselves and the world around them. Various aspects related with science are so significant for life and society that science cannot be limited as a subject. Therefore, keeping in view the importance of science, the school teachers have to essentially pay more attention to it with a changed perspective. Importance of science process skills (basic and integrated) for a person’s intellectual development and holistic development has to be emphasised in schools. In particular emphasis on scientific skill development through science education in the school curriculum has to be brought up .It necessitates to include more practical based activities (laboratory, exploratory and interdisciplinary) related to real world in the teaching–learning of the subject. The present review paper gives a brief introduction of science education, its purpose and the scientific skills which must be acquired through it in schools.